2012
DOI: 10.2147/jpr.s33112
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol/paracetamol fixed-dose combination in the treatment of moderate to severe pain

Abstract: Pain is the most common reason patients seek medical attention and pain relief has been put forward as an ethical obligation of clinicians and a fundamental human right. However, pain management is challenging because the pathophysiology of pain is complex and not completely understood. Widely used analgesics such as nonsteroidal anti-inflammatory drugs (NSAIDs) and paracetamol (acetaminophen) have been associated with adverse events. Adverse event rates are of concern, especially in long-term treatment or at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 141 publications
(103 reference statements)
0
20
0
2
Order By: Relevance
“…No serious adverse reaction was reported in the study. NSAIDs are commonly associated with GI adverse effects 20. In our study, five patients reported nine events related to GI tract.…”
Section: Discussionmentioning
confidence: 50%
“…No serious adverse reaction was reported in the study. NSAIDs are commonly associated with GI adverse effects 20. In our study, five patients reported nine events related to GI tract.…”
Section: Discussionmentioning
confidence: 50%
“…The inhibition of 5-HT and NE reuptake may account for 213 triggering two significant adverse events: seizures and serotonin 214 syndrome, particularly likely in patients receiving the drug in 215 overdose, or when co-administered with antidepressants or even 216 at the recommended dose in patients with history of epilepsy 217 [17, 26,27]. 218 Some authors hypothesized the mechanism of TrHC-induced 219 seizures.…”
Section: Q3mentioning
confidence: 99%
“…opioids are combined with non-opioid analgesic drugs that act via 289 different mechanisms and provide an additive or synergistic effect 290 [27]. For instance, clonidine and other a2-adrenergic agonists are 291 commonly used for this purpose.…”
Section: Q3mentioning
confidence: 99%
“…Tramadol with acetaminophen combination provides the potential benefits by increasing efficacy and reducing the adverse effects. Both the component have a different mechanism of action and the combination shows a synergistic effect in pain relief [18]. The goal of the therapy is to facilitate patient compliance, simplify prescribing and improve efficacy without increasing adverse effects and is achieved with combination therapy [19].…”
Section: Discussionmentioning
confidence: 99%